Giant right coronary artery aneurysm. Case Report - Benjamín Iván Hernández-Mejía; Edison Ricardo Espinoza-Saquicela (Case Reports)
Introduction: Coronary aneurysms are rare and are linked to drug abuse; symptomatology depends on the coronary anatomy. This is a case of acute coronary syndrome associated with a giant right coronary aneurysm.